2014
DOI: 10.1242/bio.201410132
|View full text |Cite
|
Sign up to set email alerts
|

CCM proteins control endothelial β1 integrin dependent response to shear stress

Abstract: Hemodynamic shear stress from blood flow on the endothelium critically regulates vascular function in many physiological and pathological situations. Endothelial cells adapt to shear stress by remodeling their cytoskeletal components and subsequently by changing their shape and orientation. We demonstrate that β1 integrin activation is critically controlled during the mechanoresponse of endothelial cells to shear stress. Indeed, we show that overexpression of the CCM complex, an inhibitor of β1 integrin activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 49 publications
(69 reference statements)
2
31
0
Order By: Relevance
“…Future research is likely to benefit from walking this two-way street, in which genes and processes involved in of flow-dependent pathways (117). Indeed, more recent data show that loss of the CCM complex induces flow-independent integrin activation (118) and that integrins are required for KLF2 induction (119). These data are again consistent with the general idea that loss of CCM proteins results in constitutive activation of a pathway that is normally regulated by flow.…”
Section: Discussionsupporting
confidence: 63%
“…Future research is likely to benefit from walking this two-way street, in which genes and processes involved in of flow-dependent pathways (117). Indeed, more recent data show that loss of the CCM complex induces flow-independent integrin activation (118) and that integrins are required for KLF2 induction (119). These data are again consistent with the general idea that loss of CCM proteins results in constitutive activation of a pathway that is normally regulated by flow.…”
Section: Discussionsupporting
confidence: 63%
“…However, no study has so far undertaken the difficult work of organizing and prioritizing the identified signaling pathways in the context of the natural history of CCM, thus each pathway presently stands as a separate entity, independent of the others. Among others, it has been shown that CCM proteins regulate cadherin-mediated cell-cell junctions (Glading et al, 2007, Glading and Ginsberg, 2010, Lampugnani et al, 2010), integrin-mediated cell-matrix adhesion (Faurobert et al, 2013, Liu et al, 2013, Macek Jilkova et al, 2014), and Rho GTPase-regulated cytoskeleton dynamics (Borikova et al, 2010, Crose et al, 2009, Richardson et al, 2013, Stockton et al, 2010, Whitehead et al, 2009, Zheng et al, 2010). …”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…More recently, it has been established that CCM proteins may also regulate integrin-based focal adhesions, which connect endothelial cells to the underlying extracellular matrix, and integrin-mediated signaling (Faurobert et al, 2013, Liu et al, 2013, Macek Jilkova et al, 2014, Renz et al, 2015). Specifically, there is evidence that CCM proteins limit β1 integrin-dependent endothelial cell adhesion, contractility, and fibronectin remodeling by stabilizing ICAP1, an inhibitor of β1 integrin (Faurobert et al, 2013, Liu et al, 2013), and may control endothelial β1 integrin-dependent mechanotransduction in response to shear stress (Macek Jilkova et al, 2014, Renz et al, 2015).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…CCM complex components play a role in controlling the response of β1 integrin signalling to blood flow in endothelial cells (Macek Jilkova et al, 2014), and the loss of CCM proteins in mouse and zebrafish results in severe cardiovascular defects (Boulday et al, 2009;Hogan et al, 2008;Kleaveland et al, 2009;Mably et al, 2003Mably et al, , 2006Renz et al, 2015;Yoruk et al, 2012;Zheng et al, 2010;Zhou et al, 2015). Although Klf2 signalling has mainly been associated with vasoprotective functions within endothelial cells in response to shear stress (Dekker et al, 2006;Lee et al, 2006;Parmar et al, 2006), or with the control of cardiac valve morphogenesis in response to reversible flows (Heckel et al, 2015;Vermot et al, 2009), it has another important function: it promotes proangiogenic signalling during zebrafish aortic arch blood vessel development (Nicoli et al, 2010).…”
Section: Mechanosensitive Pathways Within the Endocardiummentioning
confidence: 99%